The small GTPase Rac1 is a novel binding partner of Bcl-2 and stabilizes its antiapoptotic activity - Velaithan, R.; Kang, J.; Hirpara, J.; Loh, T.; Goh, B.; Le Bras, M.; Brenner, C.; Clement, M.; Pervaiz, Shazib (American Society of Hematology, 2011)
The small GTPase Rac1 is involved in the activation of the reduced NAD phosphate oxidase complex resulting in superoxide production.We recently showed that Bcl-2 overexpression inhibited apoptosis in leukemia cells by creating a pro-oxidant intracellular milieu, and that inhibiting intracellular superoxide production sensitized Bcl-2-overexpressing cells to apoptotic stimuli. We report here that silencing and functional inhibition of Rac1 block Bcl-2- mediated increase in intracellular superoxide levels in tumor cells. Using confocal, electron microscopy and coimmunoprecipitation, as well as glutathione S-transferase- fusion proteins, we provide evidence for a colocalization and physical interaction between the 2 proteins. This interaction is blocked in vitro and in vivo by the BH3 mimetics as well as by synthetic Bcl-2 BH3 domain peptides. That this interaction is functionally relevant is supported by the ability of the Bcl-2BH3peptide as well as the silencing and functional inhibition of Rac1 to inhibit intracellular superoxide production as well as overcome Bcl-2-mediated drug resistance in human leukemia cells and cervical cancer cells. Notably, the interaction was observed in primary cells derived from patients with B-cell lymphoma overexpressing Bcl-2 but not in noncancerous tissue. These data provide a novel facet in the biology of Bcl-2 with potential implications for targeted anticancer drug design. © 2011 by The American Society of Hematology.